2017
DOI: 10.1038/onc.2017.318
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PRP4K drives anoikis resistance in part by dysregulation of epidermal growth factor receptor endosomal trafficking

Abstract: Anoikis acts as a critical barrier to metastasis by inducing cell death upon cancer cell detachment from the extracellular matrix (ECM), thereby preventing tumor cell dissemination to secondary sites. The induction of anoikis requires the lysosomal-mediated downregulation of epidermal growth factor receptors (EGFRs) leading to termination of pro-survival signaling. In this study, we demonstrate that depletion of pre-mRNA splicing factor 4 kinase (PRP4K; also known as PRPF4B) causes dysregulation of EGFR traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 66 publications
5
47
0
Order By: Relevance
“…Similarly, when PRP4K is depleted in the mesenchymallike TNBC cell line MDA-MB-231, mesenchymal markers such as fibronectin, Zeb1, and Slug/SNAI2 were upregulated, as was epithelial marker Zo-1 by 2-fold (Fig 1). In previous work, we also observed the upregulation of Zeb1 following depletion of PRP4K in the epithelial-like breast cancer cell line MCF7 but this occurred without loss of E-cadherin [21]. Thus, depletion of PRP4K seems to drive partial EMT in normal mammary epithelial cell lines ( Fig 10A).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Similarly, when PRP4K is depleted in the mesenchymallike TNBC cell line MDA-MB-231, mesenchymal markers such as fibronectin, Zeb1, and Slug/SNAI2 were upregulated, as was epithelial marker Zo-1 by 2-fold (Fig 1). In previous work, we also observed the upregulation of Zeb1 following depletion of PRP4K in the epithelial-like breast cancer cell line MCF7 but this occurred without loss of E-cadherin [21]. Thus, depletion of PRP4K seems to drive partial EMT in normal mammary epithelial cell lines ( Fig 10A).…”
Section: Discussionsupporting
confidence: 62%
“…However, recent studies have linked aggressive cancer phenotypes to both mesenchymal-to-epithelial transition (MET) and developmental states caught "in-between" EMT and MET, otherwise known as partial EMT [1,5,34]. In this study, we examined the inter-relationship between EMT and PRP4K, a protein that when depleted can induce aggressive cancer phenotypes including anoikis and chemotherapy resistance [21,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted by our group suggested that the yolk sac likely does not provide the same extracellular matrix context present in a solid tumor [33]. As a result of this microenvironment feature, resistance to anoikis, a mode of programmed cell death initiated after loss of contact with the extracellular matrix, is required to support increased XT proliferation in this compartment.…”
Section: Discussionmentioning
confidence: 97%
“…Even though we could detect KSHV lytic gene products in the xenograft, it remains unclear whether this is sufficient to support production of infectious virions in situ, which will require further development of sensitive detection methods. It has been reported that the normal maintainence temperature of zebrafish (28 • C) can hinder replication of human viruses that have evolved to replicate at higher temperatures [15,33]. We have addressed this issue by housing xenotransplanted zebrafish larvae at 35 • C to enable KSHV replication.…”
Section: Discussionmentioning
confidence: 99%